Influence and mechanism of sodium-glucose cotransporter-2 inhibitors on the cardiac function: study protocol for a prospective cohort study - Cao, Min-Jia; Shi, Fang-Hong; Yu, Bin-Bin; Ma, Xue-Chen; Zhang, Chen; Xu, Li; Jiang, Yi-Hong; Ge, Heng; Shen, Long; Pu, Jun (Frontiers in Endocrinology, 2023)
Background: Acute myocadiac infarction (AMI) poses a significant threat to cardiovascular diseases (CVD), leading to high risk of heart failure (HF) and cardiovascular death. Growing evidence have unveiled the potential of sodium-glucose cotransporter-2 (SGLT2) inhibitors to improve cardiovascular outcomes in patients with CVD irrespective of diabetes, but there is limited evidence in AMI patients. Furthermore, it is controversial whether the effects can be ascribed to the amelioration of left ventricular (LV) function further complicates the understanding of their underlying mechanism. Methods: This study is a prospective, phase Ⅳ, open label, parallel group, single-center trial conducted in a large tertiary teaching hospital in China. A total of 120 patients with AMI and type 2 diabetes mellitus (T2DM) will be included. Those who received SGLT2 inhibitors are considered as the experimental group; and those taking other antidiabetic agents are considered as the control group. The primary outcome is change in LV end-systolic volume index (LVESVi) measured by cardiac magnetic resonance (CMR) imaging from baseline during one-year follow-up period. Secondary outcomes include other LV parameters such as LV mass, LV volume, and LV ejection fraction (EF); quality of life and functional capacity such as Kansas City Cardiomyopathy Questionnaire overall summary score (KCCQ-OS) and EuroQol-5-dimension (EQ-5D); biomarkers associated with diagnostic parameter of AMI and possible mechanisms on cardiovascular protection, such as creatinine kinase (CK), troponin T-level (TnT), troponin I-level (TnI), soluble suppression of tumorigenicity-2 (sST2), Galectin-3 (Gal-3), fibroblast growth factor 21 (FGF21) and microRNA (miRNA) level. Discussion: This study aims to investigate whether SGLT2 inhibitors could improve LV function by measuring CMR, quality of life and functional capacity in patients with AMI in real-world settings, providing evidence on the underlying mechanism of SGLT2 inhibitors on cardio-protection. Trial Registration: Chinese Clinical Trial Registry (ChiCTR2200065792)